Nonsteroidal Anti-Inflammatory Drug-Induced Peptic Ulcer Disease - Kyoung A Ko; Dong-Kyu Lee (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Nonsteroidal anti-inflammatory drugs (NSAIDs) are widely prescribed for their anti-inflammatory and analgesic effects; however, their prolonged use significantly contributes to peptic ulcer disease (PUD) and its complications, such as bleeding and perforation. The pathogenesis primarily involves cyclooxygenase (COX) enzyme inhibition and direct mucosal injury, leading to impaired gastrointestinal defense mechanisms. Multiple risk factors, including advanced age, a history of ulcers, and the concurrent use of anticoagulants or corticosteroids, significantly increase the risk of ulcers and related complications. Global epidemiological studies demonstrate considerable geographical variation in prevalence rates. Despite higher NSAID usage, high-income countries exhibit relatively lower rates, primarily due to well-established preventive strategies. Prevention should be based on careful risk stratification that accounts for both gastrointestinal and cardiovascular factors. Proton pump inhibitors have demonstrated superior efficacy in both prevention and treatment, while selective COX-2 inhibitors offer an alternative strategy, though they require careful cardiovascular risk assessment. The synergistic interaction between NSAID use and Helicobacter pylori infection necessitates testing and eradication, particularly in high-risk patients. NSAID discontinuation remains the primary therapeutic strategy when feasible, with studies showing significantly improved healing rates compared with continued use. Recent advances include the emergence of potassium-competitive acid blockers, which provide rapid and sustained acid suppression, offering promising alternatives for both prevention and treatment. Continued research aimed at optimizing preventive strategies and developing novel therapeutic approaches remains essential for improving clinical outcomes in NSAID-induced PUD.